Decolorization kinetics of azo dye (methyl orange) in Fenton process with high entropy alloys as catalyst - Abu Hassan, Nur Hudawiyah; Fadil, Nor Akmal; Jamal, Nur Ayuni; Mohd Daud, Farah Diana; Nordin, Norhuda Hidayah (Trans Tech Publications Ltd, Switzerland, 2023)
This study explored the decolorization kinetics of azo dye (methyl orange) with the presence of high entropy alloys (HEAs) as a catalyst in the Fenton process. The kinetic reaction of the azo dye was determined using the first and second-order kinetics model. The slope from the first pseudo kinetics model was determined to compute the decolorization rate constant (K) This present work showed that the model was significantly well fitted with the experimental data. The highest K value of HEA catalyst was occurred at 30 minutes within 60 minutes of the Fenton reaction. The obtained result also showed the efficiency of the high entropy alloys (HEAs) rapidly degraded the azo dyes.